Isolated Echogenic Cardiac Focus: Assessing Association with Trisomy 21 by Combining Results from a Prenatal Center with a Bayesian Meta-Analysis - Wrede, Elisabeth; Knippel, Alexander Johannes; Verde, Pablo Emilio; Hammer, Ruediger; Kozlowski, Peter (Ultrasound International Open, 2019)
Objective To investigate the clinical relevance of an isolated echogenic cardiac focus (iECF) as a marker for trisomy 21 using a large second-trimester collective including a low-risk subgroup.Materials and Methods We retrospectively evaluated 1 25 211 pregnancies from 2000–2016 and analyzed all iECF cases with regard to chromosomal anomalies. It consisted of an early second-trimester collective from 14+0−17+6 weeks (n=34 791) and a second-trimester anomaly scan collective from 18+0–21+6 weeks. Two a priori risk subgroups (high and low risk) of the latter were built based on maternal age and previous screening test results using a cut-off of 1:300. Likelihood ratios (LR) of iECF for the detection of trisomy 21, trisomy 13, trisomy 18 and structural chromosomal anomalies were estimated.Results In total, 1 04 001 patients were included. An iECF was found in 4416 of 1 02 847 euploid fetuses (4.29%) and in 64 of 557 cases with trisomy 21 (11.49%) giving a positive LR of 2.68 (CI: 2.12–3.2). The sensitivity was 11.5% at a false-positive rate of 4.29% (CI:4.17–4.42) with p≤0.01%. In the high-and low-risk subgroups, the prevalence of iECF was comparable: 5.08% vs. 5.05%. The frequency of trisomy 21 was 0.39%, 98/24 979 vs 0.16%, 69/44 103. LR+was 3.86 (2.43–5.14) and 2.59 (1.05–4). For both subgroups the association of iECF with trisomy 21 was statistically significant. The prevalence of structural chromosomal anomalies in the second-trimester anomaly scan collective was 0.08% (52/68 967), of which 2 showed an iECF.Conclusion The detection of an iECF at the time of 14+0–21+6 weeks significantly increases the risk for trisomy 21 in the high-risk and in the low-risk subgroups and does not statistically change the risks for trisomy 13/18 or structural abnormalitie.